USING THE LEADERSHIP TRILOGY OF KI HADJAR DEWANTARA AS THE BASIS FOR IMPLEMENTING THE FLIPPED CLASSROOM MODEL IN ELEMENTARY SCHOOLS - Maria Adventina Sunardiyah; Sutrisna Wibawa; Supriyoko Supriyoko; Moh. Rusnoto Susanto; Anselmus Sudirman (International Journal of Engagement and Empowerment, 2023)
The objectives of the study are to describe (1) the application of Ki Hadjar Dewantara's Leadership Trilogy as the foundation for creating the flipped classroom model in elementary schools and (2) as the foundation for character education as the results of the analysis regarding the efficacy of the flipped classroom learning model based on Ki Hadjar Dewantara's Leadership Trilogy in building the character profile of Pancasila students. The study method was qualitative research with a descriptive approach to analyzing the implementation process of Ki Hadjar Dewantara's Leadership Trilogy as the foundation for constructing the flipped classroom model in primary schools. The success of the flipped classroom learning model based on Ki Hadjar Dewantara's Leadership Trilogy in Elementary Schools as a foundation for character education builds up the profile characters of Pancasila students. In this study, the stages of implementation were planning, implementation, reflection, and evaluation. During the planning stage, the researcher designed learning tools implemented for the application of Civics learning, which involved participatory students in understanding and discussing teaching materials that were thoroughly explored. The findings of this study show that: (1) Using the teaching pillars of Ki Hadjar Dewantara's leadership trilogy as a foundation for constructing the flipped classroom model in primary schools can strengthen the fundamentals of character education, which affect learning achievement. (2) The flipped classroom learning model in elementary schools based on Ki Hadjar Dewantara's Leadership Trilogy in developing the character of Pancasila student profiles is very beneficial to adopt and develop into future research activities